Cellulase aided extraction and characteristics of sulfated polysaccharides from Brown seaweed (Turinaria turbinata) - Hammed, Ademola Monsur; Simsek, Senay; Jaswir, Irwandi; Amid, Azura; Alam, Md. Zahangir (2016)
Aqueous extracts, ethanolic precipitate and supernates of five brown seaweeds; Sargassum duplicatum, Sargassum binderi, Sargassum fulvellum, Padina australis and Turbinaria turbinata, were investigated for inhibition Nitric oxide (NO) production in lipopolysaccharide (LPS) induced macrophage RAW 264.7 cell line. All extracts contain high fucose and inhibit NO secretion in a dose dependent manner, precipitate of T. turbinata was highest in percentage yield 20% and dosage of 200g/ml down-regulated >80% NO secretion. Enzyme aided extraction was carried out on T. turbinata and released ethanolic precipitate was enhanced by the use of cellulase compared to vicozymes and amyloglucosidase. Eight processing conditions were screened with Plackett-Burman design and 3 significant factors (hydrolysis time, enzyme concentration and extraction stage) were optimized using Faced Centered Central Composite Design in Response Surface Methods. Increase in yield was due to substrate ruptured by cellulase and the infrared spectra of sulfated polysaccharide confirmed presence of sulfated groups. Anion exchange chromatography separation gave three fractions: TtF1, TtF2 and TtF3. TtF3 has high percentage of fucose (60.920.09 %). TtF3 inhibited NO secretion in LPS induced macrophage with IC50 value of 103.76 g/ml. Secretion of PGE2, TNF-α and IL-8 were inhibited by TtF3. Cytotoxicity assay confirmed that TtF3 was nontoxic. The molecular weight TtF1, TtF2 and TtF3 are 223.5, 495.5 and 326.05 kDa, respectively. Proton NMR signals showed that the spectra of TtF2 and TtF3 possessed α-anomeric proton (5– 5.6 ppm), ring proton (3.4 – 4.4), O-acetyl group (2.2 ppm) and methyl proton (1 – 1.3 ppm). Thermal degradation pattern of TtF1 and TtF2 were similar compared to that of TtF3. The biological and physicochemical properties of the Sulfated polysaccahrides were related. The findings confirmed the potential of brown seaweed as a viable source of anti-inflammatory compounds.